THE DEVELOPMENT OF DIGITAL LEARNING BASED ON MICROSOFT ACCESS SUBJECTS ARCHIVES TO IMPROVE STUDENT LEARNING OUTCOMES IN OFFICE ADMINISTRATION AT VOCATIONAL HIGH SCHOOL 3 SURAKARTA - Arif Wahyu Wirawan; Cicilia Dyah Sulistyaningrum Indrawati; Andre N. Rahmanto (Proceedings Education and Language International Conference, 2017)
The purpose of this study was to: 1) to determine the digital media-based learning Microsoft Access on the subjects of archives in an effort to improve the learning outcomes of students office administration SMK Negeri 3 Surakarta. 2) Determine the effectiveness of digital media-based learning Microsoft Access on the subjects of archives in an effort to improve the learning outcomes of students office administration SMK Negeri 3 Surakarta. This study is a research and development (R & D). This media development Hannafin and Peck. The subject of limited testing done for the nine students of class X AP and large scale trials conducted for thirty students of class X AP 1 in SMK Negeri 3 Surakarta. The analysis technique used descriptive qualitative and quantitative. The results showed that: (1) the media developed already worthy and qualified to be used. (2) effectiveness is find that tstatistic> ttable = (3.26> 2.00), then H0 is rejected, it means that the two groups have different learning achievement scores. Results posttest between the experimental class (using the media developed) with a control class (do not use the media developed) shows that the average value obtained by the experimental class is 80.59, the average value is higher than the control class 77, 97. The conclusion of this research is the development of digital media-based learning Microsoft Access considered effective in improving student learning outcomes office administration SMK Negeri 3 Surakarta. Keywords: Development, Digital Learning, Archive, Office Administration, Innovation in Education.